2018
DOI: 10.1002/jgc4.1056
|View full text |Cite
|
Sign up to set email alerts
|

Online decision support for persons having a genetic predisposition to cancer and their partners during reproductive decision‐making

Abstract: A nationwide pretest–posttest study was conducted in all clinical genetic centres in the Netherlands, to evaluate the effects of an online decision aid to support persons who have a genetic predisposition to cancer and their partners in making an informed decision regarding reproductive options. Main outcomes (decisional conflict, knowledge, realistic expectations, level of deliberation, and decision self‐efficacy) were measured before use (T0), immediately after use (T1), and at 2 weeks (T2) after use of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Although health professionals agreed that the current version of the decision aid is appropriate to provide to eligible couples, just over half of the health professionals indicated in the questionnaire that the decision aid fits within their routine clinical practice. The recruitment of couples for the effect study [ 14 ] occurred with flyers including unique login data for the decision aid. The experience of health professionals during this recruitment period may have contributed to the strong preference for the use of a freely accessible decision aid, as many participants indicated that they found the use of paper-based materials (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although health professionals agreed that the current version of the decision aid is appropriate to provide to eligible couples, just over half of the health professionals indicated in the questionnaire that the decision aid fits within their routine clinical practice. The recruitment of couples for the effect study [ 14 ] occurred with flyers including unique login data for the decision aid. The experience of health professionals during this recruitment period may have contributed to the strong preference for the use of a freely accessible decision aid, as many participants indicated that they found the use of paper-based materials (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, no initiatives to support couples with a predisposition to hereditary cancer in the decision-making regarding their wish to have children have been reported in the literature. The present study is part of a larger study on the development, evaluation, and implementation of an online decision aid with the aim of supporting persons having a genetic predisposition to cancer and their partners in making an informed reproductive decision [ 12 14 ]. The decision aid is meant for couples who have a high genetic risk, mostly 50%, due to autosomal dominant inheritance, of transmitting a pathogenic variant to offspring with a high risk of a future malignancy (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study is part of a larger project on the development and implementation of an online decision aid with the aim of supporting couples who are aware that one of them has a genetic predisposition to cancer, to decide on the personally most suitable reproductive option (Reumkens et al 2018 ; Reumkens et al 2019a ). In a previous study, short-term effects of the online decision aid in supporting informed reproductive decision-making among our target group were investigated (Reumkens et al 2019b ). In this study, we report on the effects on informed decision-making by both partners.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, level of deliberation and decision self-efficacy improved for those with low baseline levels. 66 These findings support the use and continued optimization of decision support tools in reproductive counselling of couples with hereditary cancer. It is advised to provide this form of decision support in addition to general counselling.…”
Section: Timing Of Information Provisionmentioning
confidence: 62%